2004
DOI: 10.1007/s00120-004-0714-3
|View full text |Cite
|
Sign up to set email alerts
|

Positronenemissionstomographie (PET) zur Diagnostik und zum Therapiemonitoring bei urologischen Tumoren

Abstract: Positron emission tomography (PET) using ((18)F)2-fluoro-D-2-desoxyglucose (FDG) has been shown to be a highly sensitive and specific imaging modality in the diagnosis of primary and recurrent tumors and in the control of therapies in numerous non-urologic cancers. It was the aim of this review to validate the significance of PET as a diagnostic tool in malignant tumors of the urogenital tract. A systematic review of the current literature concerning the role of PET for malignant tumors of the kidney, testicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
1
5
0
Order By: Relevance
“…18 F-FDG is not specific to tumor metabolism and can accumulate in metabolically active inflammatory cells; however, the usefulness of 18 F-FDG in human prostate adenocarcinoma is unclear. Some investigators have reported low uptake of 18 F-FDG in patients with prostate cancer, whereas in other studies, 18 F-FDG PET/CT scans have been used to identify osseous and soft-tissue metastasis from prostate adenocarcinoma (17,18,(35)(36)(37). Our data demonstrated early tracer uptake (2 wk) and a strong correlation between soft-tissue tumor burden measurements with 18 F-FDG.…”
Section: Discussionsupporting
confidence: 45%
“…18 F-FDG is not specific to tumor metabolism and can accumulate in metabolically active inflammatory cells; however, the usefulness of 18 F-FDG in human prostate adenocarcinoma is unclear. Some investigators have reported low uptake of 18 F-FDG in patients with prostate cancer, whereas in other studies, 18 F-FDG PET/CT scans have been used to identify osseous and soft-tissue metastasis from prostate adenocarcinoma (17,18,(35)(36)(37). Our data demonstrated early tracer uptake (2 wk) and a strong correlation between soft-tissue tumor burden measurements with 18 F-FDG.…”
Section: Discussionsupporting
confidence: 45%
“…There were six publications obtained from more than one of the databases (13Á18). Three publications in non-English language were excluded: one in German (16), one in French (19), and one in Czech (20). There were thus 44 publications for further analysis (Fig.…”
Section: Results Of Different Publicationsmentioning
confidence: 99%
“…Positron emission tomography has shown prominent features compared with other molecular imaging approaches. PET can trace suspicious malignant lesions and provide functional imaging of those areas, which is useful for early diagnosis of diseases ( Kang et al, 2004 ; Machtens et al, 2004 ). Although magnetic resonance imaging (MRI) has a higher resolution, the specificity of its related contrast agents for β cells is not as good as PET imaging.…”
Section: Future Perspectivesmentioning
confidence: 99%